Book review: Urban environments in Africa - A critical analysis of environmental politics - Oliveira, Eduardo (My University, 2019)
By 2030, the fastest rates of population growth and urbanisation will be witnessed in sub-Saharan Africa, followed by India and parts of Southeast Asia (Nagendra et al., 2018). Academic literature (Shoffner et al., 2018) as well as policy documents (UNDP, 2018) have been acknowledging that urbanisation is a global phenomenon with strong environmental sustainability implications and cities have become central to ensuring a sustainable future (Acuto et al., 2018). In ‘Urban Environments in Africa’, Garth Myers deconstructs the criticisms of urban political ecology (UPE) and investigates African environmentalism from different ontological and epistemological points of view.
Keywords: African cities; book review; resilience; sustainability; urban environment; urban planning